Graphite Recycling from End‐of‐Life Lithium‐Ion Batteries: Processes and Applications. Issue 2 (15th June 2022) - Abdollahifar, Mozaffar; Doose, Stefan; Cavers, Heather; Kwade, Arno
Abstract: The number of lithium‐ion batteries (LIBs) from hybrid and electric vehicles that are produced or discarded every year is growing exponentially, which may pose risks to supply lines of limited resources. Thus, recycling and regeneration of end‐of‐life LIBs (EoL‐LIBs) is becoming an urgent and critical task for a sustainable and environmentally friendly future. In this regard, much attention, especially in industry, is expended for developing recycling of cathode materials and the other valuable materials, but not much attention is dedicated to the recycling and reuse of graphite (Gr) from EoL‐LIBs. Herein, the current status of EoL‐LIB regeneration is summarized, with a focus on the recycling and purification of Gr, a state‐of‐the‐art anode material for most of the commercial LIBs. According to the recent advances regarding Gr recycling, three major regeneration processes of Gr are categorized, including i) washing Gr with different solvents, ii) thermal treatment process, and iii) hybrid (chemical and thermal) treatment processes. Depending on the source of the LIBs, and the method and quality of separation and purification, the recycled Gr can be reutilized as an active material for battery industries, including graphene production, as well as many other alternative applications, which are also addressed here. Abstract : With the increasing number of hybrid and electric vehicles, the recycling of end‐of‐life Li‐ion batteries (Eol‐LIBs) is a serious task for a sustainable and environmentally friendly society. This review focuses on outlining the way forward to improve the recycling of Eol‐LIBs, through recovery and purification of graphite, with the introduction of regeneration processes.